Pendekatan Geopolitik Terhadap Kekuatan Strategis Keamanan Nasional Indonesia dalam Menyikapi Rivalitas AS–China di Asia Tenggara: Penelitian - Titik Khusumawati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Geopolitical rivalry between the U.S. and China in Southeast Asia significantly impacts regional stability and Indonesia’s strategic interests. This study analyzes Indonesia’s strategic national security capacity in responding to the rivalry using four geopolitical dimensions: military, diplomacy, economy, and technology. Based on a literature review of indexed academic sources, the findings reveal that Indonesia adopts a hedging strategy—balancing interests between both powers while maintaining foreign policy autonomy. Its strategic geographical position, including the Malacca Strait and North Natuna Sea, makes Indonesia a key actor in regional stability. However, internal challenges persist, such as defense capability gaps, suboptimal defense diplomacy, and foreign influence vulnerabilities. The study recommends strengthening regional diplomacy, modernizing defense systems, and enhancing maritime resilience. Economically, engagement in the Belt and Road Initiative (BRI) and strategic technology partnerships with Western countries improve Indonesia’s global leverage. Ultimately, Indonesia’s success in maintaining national security lies in its ability to integrate internal and external strengths adaptively without falling into strategic dependency. These findings have important implications for future defense, foreign policy, economic development, and cybersecurity strategies.